Construction of a questionnaire for measure the learning difficulties of Arabic language for non-Arabic speaking students - Farihah Muftah al-Ganzouri; Kamarulzaman Abdul Ghani (Faculty of Education, Universiti Kebangsaan Malaysia, 2011)
One of the most common problems faced by researchers in the field of learning Arabic a lack of standards educational measure and test in measuring difficulties of learning language among non-native speakers away from the written and oral tests. Therefore the intention in the preparation of these standards is the main concerns for those are involved in the field of education which they found a few studies that focused on building standards measurement of the learning Arabic language difficulties. Most of the studies was adopted on the written examinations to measure these difficulties, which makes the responsible of the difficulties measurement on one side of several components of the language. So it is an obligation on the educators to work on the design of standardized measures that help to identify the difficulties of learning Arabic language for non-native speakers students and this study is regarding to this focused issue. The study aims to develop a questionnaire to measure the difficulties of learning Arabic language and the questionnaire contains 54 items include the difficulties of reading, writing, speaking, comprehension and the difficulties of grammar and morphology. The sample of the pilot study consisted of 90 people divided between the teachers and students that studying at the first, second, third and fourth year of the Department of Arabic Language and Literature, Dakwah, Civilization, and The Holy Quran and Quranic Sciences. The study found a coefficient of validity and reliability of the instrument is high that be able to use in the other studies.